RELAKSASI DZIKIR UNTUK MENINGKATKAN KESEJAHTERAAN SUBJEKTIF REMAJA SANTRI - Iwan Martin; Sartini Nuryoto; Siti Urbayatun (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2018)
The aim of this study was to determine the effect of relaxation with dzikir to improve the subjective well-being of adolescent students at muslim school. The adolescent students at muslim school shall be referred to as adolescent santri. This study was an experimental research with randomized pretest-posttest control group design. Quantitative analysis test was performed using SPSS for windows 16.0 while observation and interview technique was used to get additional data. The subjects of this study were students at muslim school of 12-16 years old. In the study group consisted of experimental and control groups. The experimental group received relaxation with dzikir training for four meetings with the duration of each meeting 1-2 hours. The scale of subjective well-being is adapted from the SWLS scale (satisfaction with life scale) developed by Diener, Emmons, Larsen, and Griffin (1985), and the positive and negative affect schedule from Watson, Clark, and Tellegen (1988). Data were analyzed using t-test based on gain score. The results showed that there was a significant difference in subjective well-being between experiment and control group Sig (p) = 0.001 (p <0.01). The conclusions showed that the level of subjective well-being of the adolescent have increased after being given the intervension of relaxation with dzikir. These results are also supported by observational and interview data that indicated that in general the participants in the intervention reported perceived change after the training, such as the feeling of feel restful, more comfortable, relieved, confident, eager, and more grateful to God’s favor. Keywords: adolescent santri, relaxation with dzikir, subjective well-being.